Isolated Central Nervous System Circuits - Ballanyi, Klaus.; Ballanyi, Klaus. (Neuromethods, 2012)
Advances in methodologies and experimental models are pivotal to furthering our understanding of central nervous system (CNS) functions in mammals. Isolated Central Nervous System Circuits examines the application a variety of technologies to mostly active in vitro preparations from basically different CNS regions with a diversity of functions.  From patch-clamp, multiphoton imaging, live fluorescent protein expression, or immunohistochemistry techniques to acute or 'organotypic' slices and en bloc preparations, this detailed volume features key protocols and examples for exciting results from the labs of renowned experts.  Written for the popular Neuromethods series, chapters include the kind of thorough implementation advice that is vital for achieving successful results.   Comprehensive and cutting-edge, Isolated Central Nervous System Circuits will greatly aid scientists to further improve models and to develop corresponding models of not yet intensively studied structures such as nucleus ruber, superior colliculus, or basal ganglia.